Pattern and process: the language of landscape ecology - Catherine Alington (Landscape Review, 1997)
Landscape architecture and landscape ecology are fundamentally concerned with the connections between landscape pattern and ecological process. Landscape ecologists typically assume that process creates pattern; landscape architects address pattern with the hope that process will follow. Whether pattern drives process or vice versa is a debate that has not been resolved, but an understanding of the complexities of the relationship is vital if pattern, process, or both are to be manipulated to achieve specific goals. That there is a relationship between pattern and process is a fundamental premise of landscape ecology, but research suggests the relationship is not straightforward. In this paper I present a brief overview of some of the major threads of this research, including some more recent theoretical advances in ecology (sensitivity to initial conditions, contingency and chaos theory) that affect the pattern/process relationship, issues of scale dependence and some of the methods used to determine pattern at various scales. I use a case study of a forested landscape in south-eastern Colorado, USA, to illustrate the complexity of the relationship between landscape pattern and disturbance process. The study demonstrates how this kind of research can provide guidelines for land managers aiming to reintroduce natural processes into a managed landscape. The study also serves to highlight the difficulties of using pattern as a surrogate for process. Understanding the relationship between pattern and process is of critical importance whether we are attempting to rehabilitate degraded landscapes, or to design management strategies for sustaining present landscape conditions, or to anticipate the effects of change in the intensity, frequency or extent of land use.